Local Government and its Role in Women’s Empowerment - Sunar, Okil (Journal of Gurubaba, 2024)
This study entitled "Local Government and its Role in Women’s Empowerment" was conduct at Brindranagar 3 Surkhet" The main objectives of the study was to find out the existing condition of Women’s empowerment and indentify the role of local level government of Women’s empowerment. The study had applied descriptive types of research design with quantitative data. This study was based on primary data. Among 1120 married of age 15-60 years Women’s out of 112 Women’s were taken systematic sampling method. Majority of 39 percent of respondents were involved in service. Similarly, 30 percent of respondents were associated with business. On the other hand so the present position of participation of local government of Women’s in self decision making power is very poor. Most of the Women’s depend decided to their husband and other person. They had mainly faced lack of decision making power in the social, economic, political. Participation of Women’s in every sector is essential to achieve national goal and in order to make society civilized. Manage the maximum quota of scholarship in secondary, higher secondary level with the Women’s of donor agencies and government authorities. Make a strict rules and regulation about the Women’s empowerment by the government.